2006
DOI: 10.1007/bf03075186
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Study of Physician Treatment Decisions for Demented Nursing Home Patients Who Develop Pneumonia

Abstract: PURPOSEWe wanted to explore factors that infl uence Dutch and US physician treatment decisions when nursing home patients with dementia become acutely ill with pneumonia.METHODS Using a qualitative semistructured interview study design, we collected data from 12 physicians in the Netherlands and 12 physicians in North Carolina who care for nursing home patients. Our main outcome measures were perceptions of infl uential factors that determine physician treatment decisions regarding care of demented patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 21 publications
0
38
1
Order By: Relevance
“…Compared to expert views, practitioners' perceptions might vary more (9) and may also differ between countries because of greater influence of different health care systems and environments in which professionals operate locally. For example, in comparative studies, physicians' presence, certainty of family wishes and perceived responsibility for decision making (or paternalism) were greater in the Netherlands compared with the US and this may translate into different treatment approaches (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to expert views, practitioners' perceptions might vary more (9) and may also differ between countries because of greater influence of different health care systems and environments in which professionals operate locally. For example, in comparative studies, physicians' presence, certainty of family wishes and perceived responsibility for decision making (or paternalism) were greater in the Netherlands compared with the US and this may translate into different treatment approaches (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…The variation between different countries' approaches to end-of-life care can be attributed to how end-of-life care is organised (particularly in nursing homes) and the legal and social understanding of end-of-life decision making, which in turn reflects both professional and family values (Helton et al, 2006). A Dutch study of 35 patients concluded that because the clinical course of dementia was considered normal, artificial administration of fluids and food was rare (The Anne Mei, 2002).…”
Section: Dementia Care Towards the End Of Lifementioning
confidence: 99%
“…However, the review demonstrated how contextual factors such as level of education, rural or urban settings and nationality all influence individuals' responses to decision making about place of care and interventions at the end of life (Caron et al, 2005a(Caron et al, , 2005bChen et al, 2006;Gessert et al, 2006). Very few studies have engaged with how carers interact with professionals in the decision-making process, nor have they described what is required for effective communication (Caron et al, 2005b) even though it is clear that how physicians resolve and negotiate patient and family preferences regarding care appears to directly influence patient outcomes (Helton et al, 2006). In the absence of agreed guidelines, and advance care plans, decision making for people with dementia at the end of life is shaped by differences in religious beliefs, professional training, understanding of the disease, what is meant by palliative care, perspectives of other patients, culture and beliefs (Luchins and Hanrahan, 1993;Cavalieri et al, 2002;Hinkka et al, 2002;The Anne Mei, 2002;Lacey, 2005;Haydar et al, 2004;Rurup et al, 2006).…”
Section: Decision Making At the End Of Lifementioning
confidence: 99%
“…Significant differences between the Netherlands and the U.S.A. were found only in two generally-worded items on nursing care and medical care, and in an item on decision-making that suggested that the respondent made decisions on her/his own. This item was frequently rated as "not applicable" and may not apply well to a shared decision-making model employed in the Netherlands (Helton et al, 2006). Reported mean SWC scores in CASCADE were not obtained during the last three months of life, but were nevertheless very similar to those we found in our study (31.9, SD 4.7 in the Netherlands, and 30.4, SD 6.1 in the U.S.A): 31.0, SD 4.2 (Engel et al, 2006) and 30.9, SD 4.1 in a broader sample .…”
Section: Satisfaction With Carementioning
confidence: 99%
“…For example, studies on pneumonia in nursing home residents with dementia identified major differences between U.S. and Dutch care (van der Steen et al, 2004;Helton et al, 2006). Dutch nursing home physicians are on-staff and usually know the residents and their family well, long before the death is imminent (Hoek et al, 2000;Helton et al, 2006).…”
Section: Introductionmentioning
confidence: 99%